Psychoanalysis and the family in twentieth-century France : Françoise Dolto and her legacy - Bates, R. (Richard) (Book collections on Project MUSE., 2022)
In the last quarter of the twentieth century, if French people had a parenting problem or dilemma there was one person they consulted above all: Francoise Dolto (1908-88). But who was Dolto? How did she achieve a position of such influence? What ideas did she communicate to the French public? This book connects the story of Dolto's rise to two broader histories: the dramatic growth of psychoanalysis in postwar France and the long-running debate over the family and the proper role of women in society. It shows that Dolto's continued reputation in France as a liberal and enlightened educational thinker is at best only partially deserved and that conservative and anti-feminist ideas often underpinned her prominent public interventions. While Dolto retains the status of a national treasure, her career has had far-reaching and sometimes harmful repercussions for French society, particularly in the treatment of autism.